The Effect of Online Customer Review and E-Service Quality on Consumer Purchase Decisions on the Marketplace Shopee in Bandar Lampung - Intan Lidiya WIduri; Mahrinasari MS; Mudji Rachmat Ramelan (Inovbook Publications, 2022)
The phenomenon of online shopping in the modern era continues to increase, so it is not surprising that business people need to pay attention to the importance of online customer reviews and provide the best quality e-service for customers to purchase products in the marketplace. One of the marketplaces that can be used is Shopee. The type of data used in this study is primary data obtained from the results of respondents' answers which were collected with the help of a questionnaire. The number of samples in this study were 120 respondents. The sampling method used purposive sampling, which is a technique to determine the sample with the appropriate criteria determined by the researcher. The analytical method used in this study is the validity test, reliability test, analysis stage using multiple linear regression, and hypothesis testing, namely the t test and the coefficient of determination (R2) test, with the help of the IBM SPSS 26 for windows application program. The results of this study indicate that the online customer review variable has a positive and significant effect on the purchasing decision variable. The e-service quality variable also has a positive and significant effect on the purchasing decision variable. In this study, the independent variable was able to explain the dependent variable by 49.8% while the rest was influenced by other variables outside the variables in this study.